2016
DOI: 10.1042/cs20150592
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell tolerance to lipopolysaccharide challenge is induced by monophosphoryl lipid A

Abstract: Prior exposure to lipopolysaccharide (LPS) produces a reduced or “tolerant” inflammatory response to subsequent challenges with LPS, however the potent pro-inflammatory effects of LPS limit its clinical benefit. The adjuvant Monophosphoryl lipid A (MPLA) is a weak toll-like receptor 4 (TLR4) agonist that induces negligible inflammation but retains potent immunomodulatory properties. We postulated that pre-treatment with MPLA would inhibit the inflammatory response of endothelial cells to secondary LPS challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…Based on previous studies, LPS causes limited production of IP-10, owing to poor induction of the TRIF pathway after TLR4 stimulation in endothelial cells. 19 However, as shown in Fig 3 B (and Fig S1 C ), when both types of endothelial cells were primed with Poly I:C, there was a significant induction of IP-10 with a greater than 17-fold increased level compared to unprimed cells in HMVECs and greater than 7-fold in HUVECs. Moreover, priming by Pam3Csk4 reduced IP-10 production by LPS rechallenge compared to unprimed cells in HMVECs, though this effect was not as significant as LPS priming.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Based on previous studies, LPS causes limited production of IP-10, owing to poor induction of the TRIF pathway after TLR4 stimulation in endothelial cells. 19 However, as shown in Fig 3 B (and Fig S1 C ), when both types of endothelial cells were primed with Poly I:C, there was a significant induction of IP-10 with a greater than 17-fold increased level compared to unprimed cells in HMVECs and greater than 7-fold in HUVECs. Moreover, priming by Pam3Csk4 reduced IP-10 production by LPS rechallenge compared to unprimed cells in HMVECs, though this effect was not as significant as LPS priming.…”
Section: Resultsmentioning
confidence: 68%
“…18 Further confounding these results, we have demonstrated that the mechanisms of TLR4 signaling tolerance in endothelial cells are differentially regulated compared to those of leukocytes, suggesting that modulation of TLR signals in human endothelial cells may not be conserved to that reported in mouse macrophages. 19 Understanding this difference in the human endothelium is emphasized by the role it plays in vascular homeostasis and innate immunity activation, making its modulation a key driver of the host response to infection. 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toll-like receptors complex (TLRs) signalling pathways, particularly TLR4, are activated by LPS, which induces excessive expressions of inflammatory cytokines [26]. We next determined whether TLR4 was involved in the anti-inflammatory roles of VH on EA.hy926 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The role of EC as inflammatory contributors to atherosclerosis is well established [44,67], and the role of myeloid trained immunity in the disease is also gaining attention (reviewed in [68,69]. These publications and others [34,37,40,48,70] acknowledge the dangers of innate over-aggressive inflammatory responses based on priming by endogenous mediators. DAMPs and other host products inducing this high alert state may lead to chronic inflammatory conditions because they will tend to favour sustained inflammatory responses rather than resolution of inflammation.…”
Section: Role Of Stromal Memory In Infection and Chronic Inflammatorymentioning
confidence: 99%